Influência da velocidade de circulação do leite na adesão de Pseudomonas aeruginosa sobre aço inoxidável - FIGUEIREDO, Hamilton Mendes de (2015)
The influence of the flow milk circulation in the bacterial adhesion of Pseudomonas aeruginosa was evaluated by simulation tests through a circuit model of milk processing. The circuit is composed of a tubulation of stainless steel AISI 304, with 1.9 cm of diameter, 5.8 m of length and a tank of 25 L used as the reservoir of the product and sanitizer solutions. The reservoir was coupled to a centrifugal bomb of ½ HP to impel the food or sanitizer solutions for the system equipped with 90º and T cylindrical stainless steel specimens. The speed of circulation values were 0.5, 1.0 and 1.5 m.s–1, corresponding to turbulent flow with number of Reynolds 14.000, 28.000 and 42.000, respectively. When flow of 0.5 m.s–1 was used 10.7% the cells remained adhered, however at the speed values of 1.0 and 1.5 m.s–1 the adhesion percentages were 5.36 and 4.9%, respectively. These findings indicate a lower removal rate of adhered cells as flow decreases allowing higher number of bacteria to adhere to the production line, which can favor the biofilm formation.